2008
DOI: 10.1007/s11199-007-9358-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Children’s Hero Attributions: Personal Hero Choices and Evaluations of Typical Male and Female Heroes

Abstract: The current study investigated gender differences in the personal hero choices, hero attributions, and characteristics attributed to "typical" male and female heroes of children living in the Midwestern United States (N=103; mean age=10 years). Questionnaires were completed in a school setting. The majority of girls chose heroes personally known to them; boys chose personal and public figures equally often. Most boys chose same gender heroes; girls' nominations were mixed. Gender differences were also seen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Galbo (1984) carried out a review of the literature and found that the data indicated a pattern of same-sex preferences, with parents being the adults selected more often. Similarly, Freedman-Doan and Eccles (1996) and Holub, Tisak, and Mullins (2008) also found that girls tended to choose females as known heroes, and boys tended to choose males when choosing within the personal domain.…”
Section: Adolescent's Choice Of Heroes and Known Adultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Galbo (1984) carried out a review of the literature and found that the data indicated a pattern of same-sex preferences, with parents being the adults selected more often. Similarly, Freedman-Doan and Eccles (1996) and Holub, Tisak, and Mullins (2008) also found that girls tended to choose females as known heroes, and boys tended to choose males when choosing within the personal domain.…”
Section: Adolescent's Choice Of Heroes and Known Adultsmentioning
confidence: 87%
“…According to this, heroes would not only be role models for adolescents (Martorell 2000) but also a reflection of their gender-role ideologies (Block 1983;Gibbons and Stiles 2004). In this regard, several studies have corroborated that heroic characteristics often reflect gender-based social attributes (Holub, Tisak, and Mullins 2008;Gash and Dominguez 2009). However, depending on the study, these dimensions carry different labels: among them, individual masculine (e.g.…”
Section: Adolescent's Choice Of Heroes and Known Adultsmentioning
confidence: 95%
See 3 more Smart Citations